On the socio-spatial embeddedness of business firms - Oinas, Päivi (ERDKUNDE, 1997)
This article stems from the obvious need in the economic geography literature to understand and conceptualise the relations of firms to their local and regional environments and thus to be better equipped to understand the key agents in processes of regional development. For this purpose, the presently popular Granovetterian notion of embeddedness is employed. The article aims to understand to which extent the notion might be helpful in gaining more understanding on the nature of firm-environment relations. Granovetter’s contribution and its application in the geographical literature are discussed, and the key elements of embeddedness are identified and scrutinised. It is concluded that even though the notion of embeddedness remains vague, it directs our attention to aspects in the relations of firms and their socio-spatial environments that are neither understood nor conceptualised very well to date. Such aspects may crucially affect the competitiveness of firms and the development of regions. Yet, in order to gain fuller understanding of the issues at play, the notion of embeddedness has to be complemented by more penetrating concepts and theorisations.